2000
DOI: 10.1071/ar99102
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Leu127 variant of the bovine growth hormone (bGH) gene with increased yield of milk, fat, and protein in Australian Holstein-Friesians

Abstract: The occurrence of the Leu127/Val127 variants of the bovine growth hormone (bGH) gene and their effect on milk production traits was investigated in Australian Holstein-Friesian cattle. Animals were genotyped for the Leu127/Val127 variants, with RFLP methodology, using PCR and AluI digestion of PCR products (AluI-RFLP). Alleles Leu127 and Val127 occurred with frequencies of 82% and 18%, respectively. The quantitative effect of this polymorphic site on milk-production traits was estimated from lactation data and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 0 publications
3
7
1
2
Order By: Relevance
“…We found allele frequencies of p L =0.850-0.920 for leucine and q V =0.080-0.150 for valine, which are in agreement with those previously reported in the Holstein-Friesian breed (Lucy et al, 1993;Shariflou et al, 2000;Kovács et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found allele frequencies of p L =0.850-0.920 for leucine and q V =0.080-0.150 for valine, which are in agreement with those previously reported in the Holstein-Friesian breed (Lucy et al, 1993;Shariflou et al, 2000;Kovács et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…A polymorphic site of the GH gene (AluI polymorphism) that results in an amino acid change at position 127 of the protein chain (leucine, L to valine, V; Lucy et al, 1991) has been linked to milk production traits with various outcomes. Some authors favored the leucine (Shariflou et al, 2000;Dybus, 2002) or the valine allele (Grochowska et al, 2001;Zwierzchowski et al, 2002;Kovács et al, 2006), while Yao et al (1996) and Lechniak et al (2002) were not able to prove any association. Endocrine characteristics of the different genotypes have also been investigated and yielded contradictory results.…”
Section: Introductionmentioning
confidence: 95%
“…These differences could be because of sample size and sampling error. Inter-and intrabreed variations with those previously reported in other taurine breeds were found to be an agreement in frequencies of growth hormone polymorphic variants (Lucy et al 1993;Grochowska et al 1999;Shariflou et al 2000;Kovacs et al 2006).…”
Section: R E S U Lt S a N D Discussionsupporting
confidence: 87%
“…Sabour and Lin (Sabour & Lin, 1996), in turn, found that the V allele of the GH gene was preferable in terms of increasing the milk yield obtained from cows. On the contrary, Shariflou with coauthors (Shariflou et al, 2000) showed greater contribution of L allele to increase of milk yield in cows. Lucy with coauthors (Lucy et al, 1993) came to the same opinion in relation to the milk productivity of Holstein in USA, while the influence of the V allele was most pronounced in the Jersey cattle breed.…”
Section: 1discussionmentioning
confidence: 94%